PRECATACLYSMIC VARIABLES: OBSERVATIONAL DATA AND MODELS - Pustylnik, I. B.; Pustynski, V. F. (Одеські астрономічні публікації, 2017)
We summarize the first results of modelling light curves of precataclysmic binaries with strong reflection effect. Our approach is based upon modified Napier’s technique and explicit computation of emergent radiation intensity using the source functions given by Strittmatter and Sobieski.